Will uterine fibroids be operated less frequently? - Jakiel, Grzegorz; Słabuszewska-Jóźwiak, Aneta; Czekańska-Rawska, Magdalena; Rawski, Wojciech; Baran, Arkadiusz; Bińkowska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2013)
Uterine fibroids are one of the most common pathologies of the female reproductive system, which may cause abnormal, heavy bleeding and pelvic pain. These ailments often prompt women to consult their gynecologists. Pharmacotherapeutic options in uterine fibroids are limited. The studies conducted so far have assessed the efficacy of progestogens, levonorgestrel-releasing intrauterine systems, antifibrinolytic agents, non-steroid anti-inflammatory drugs, GnRH analogues and Selective Progesterone Receptor Modulators (SPRMs) in the treatment of fibroid symptoms. Few agents available on the market have been approved for symptomatic treatment of uterine fibroids; these include GnRH analogues and, recently, ulipristal acetate (SPRM). The treatment with GnRH analogues as a alternative to surgery, proved unsatisfactory. Treatment duration cannot exceed 6 months due to rapid demineralization of bones associated with decreased estrogen levels. Once GnRH analogues are discontinued, fibroids start growing again, almost reaching their baseline size, while most women experience the recurrence of symptoms. Ulipristal acetate may prove a true therapeutic alternative to such technically complicated procedures as laparoscopic myomectomy or uterine artery embolization. The sustainable therapeutic effect and favorable safety profile are important characteristics of ulipristal acetate distinguishing it from other drugs. The results of studies conducted to date demonstrate that after treatment termination, surgery has been abandoned in about half of patients. Follow-up of patients who discontinued ulipristal acetate showed sustained improvement in bleeding control, pain and quality of life. Myomectomy is only indicated in symptomatic uterine fibroids, depending on their size and number; it may be an endoscopic procedure or it may require laparotomy. The choice of treatment method and scope of therapy should take into account not only clinical symptoms but also expectations of women who wish to maintain their fertility and femininity, which is related to the fact of having their uterus intact.